Gallbladder sludge and microlithiasis disappearance in a cystic fibrosis patient 1 year after triple combination therapy initiation - Corrado Tagliati; Daniele Veri; Andrea Pietra; Giuseppe Lanni; Davide Battista; Marco Fogante; Giulio Argalia; Cecilia Lanza; Stefano Pantano; Francesca Collini; Maria Di Sabatino; Pietro Ripani (Clinical Case Reports)
Key Clinical Message Gallstones, microlithiasis, gallbladder sludge, and micro‐gallbladder are frequently reported in cystic fibrosis patients, and modulators could modify gallbladder disease, probably reducing biliary secretions viscosity.